Hubungan Aktivitas Fisik Dengan Kejadian Obesitas Pada Anak Usia Sekolah : Literature Review - Raden Roro Tiya Ayu Pradika; Armenia Daih Sari; Istinengtyas Tirta Suminar (STIKES Citra Delima Bangka Belitung, 2022)
Obesity is an excessive accumulation of fat due to an imbalance in energy intake with energy used (energy expenditure) for a long time. A lifestyle of lack of physical activities accompanied by excessive eating patterns, namely high intake of carbohydrates, fat, protein and low fiber can cause obesity. This study aims to determine the relationship between physical activities and the incidence of obesity in school-age children based on literature searches. This research was a literature review research with a cross sectional study. The data used consisted of six journals in Indonesian and English which could be accessed in full-text. This study used six national and international articles, the search for articles was carried out using the keywords physical activities, obesity, and school-age children. Articles were searched through Google Scholar, Garuda Portal and PubMed. The six articles were used as material for analyzing the conditions of physical activities, obesity and knowing the relationship between the two. Light physical activities caused energy output to be low, resulting in an imbalance. Obesity was very detrimental to the quality of life of children and the results of this study indicated a relationship between physical activities and obesity. This study showed that five of the six articles studied indicated a significant relationship between physical activities and the incidence of obesity in school-age children. Nursing science is expected to be able to improve health services and health workers are able to provide information and interventions. Future researchers are expected to be able to carry out further research related to intervention and it is hoped that parents and teachers can control children to do physical activities.